1994
DOI: 10.1111/j.1438-8677.1994.tb00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentation of Zinc in Roots and Leaves of the Zinc Hyperaccumulator Thlaspi caerulescens J & C Presl

Abstract: Thlaspi caerulescens is a metallophyte that is able to hyperaccumulate Zn. In the present study the subcellular compartmentation of Zn was investigated in roots and leaves of this species by means of X‐ray microanalysis. Leaves accumulated higher average Zn concentrations than roots. In roots of plants exposed to 10 μM Zn, Zn concentrations in the apoplast were similar to those in vacuoles, while in plants treated with 100 μM Zn considerably higher Zn concentrations were detected in vacuoles than in the apopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
114
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 19 publications
15
114
1
Order By: Relevance
“…Preferential accumulation of Zn in the leaf epidermis has previously been observed in the Zn hyperaccumulator Thlaspi caerulescens (Küpper et al, 1999;Vázquez et al, 1994). Our studies demonstrated that preferential distribution of Zn and Cd was also observed in epidermal cells of stem or leaf in S. alfredii (unpublished data).…”
Section: Cellular Distribution Of H 2 O 2 In Leavessupporting
confidence: 61%
“…Preferential accumulation of Zn in the leaf epidermis has previously been observed in the Zn hyperaccumulator Thlaspi caerulescens (Küpper et al, 1999;Vázquez et al, 1994). Our studies demonstrated that preferential distribution of Zn and Cd was also observed in epidermal cells of stem or leaf in S. alfredii (unpublished data).…”
Section: Cellular Distribution Of H 2 O 2 In Leavessupporting
confidence: 61%
“…Because one of the major storage sites for Zn is the leaf vacuole (Vázquez et al, 1994), we investigated the possibility that Zn influx across the leaf cell plasma membrane was stimulated in T. caerulescens. We found that at lower Zn concentrations (10 and 100 m), there were no differences in 65 Zn uptake into leaf sections or protoplasts isolated from the two Thlaspi species.…”
Section: Discussionmentioning
confidence: 99%
“…Thlaspi caerulescens seeds were obtained from plants grown near a Zn/Cd smelter in Prayon, Belgium (Vázquez et al, 1994). Seeds were grown hydroponically in 5-L black plastic tubs as described previously (Lasat et al, 1996).…”
Section: Plant Materialsmentioning
confidence: 99%
“…These results suggest that hyperaccumulation might be a complex trait, with uptake, internal transport and tolerance being at least partly under independent genetic control. Transmembrane metal transporters may be decisively involved in uptake, xylem loading and unloading (Lasat, Baker & Kochian 1998) and vacuolar sequestration of heavy metals, particularly in the leaf epidermal cells (Vázquez et al 1994;Küpper, Zhao & McGrath 1999), trichomes (Krämer et al 1997), or stomatal guard cells (Heath, Southworth & Dallura 1997). The molecular basis of Zn uptake and transport in plants is, as yet, largely unexplored.…”
mentioning
confidence: 99%